Migrant women living with HIV in Europe: are they facing inequalities in the prevention of mother-to-child-transmission of HIV?: The European Pregnancy and Paediatric HIV Cohort Collaboration (EPPICC) study group in EuroCoord*. (25th April 2017) - Favarato, G; Bailey, H; Burns, F; Prieto, L; Soriano-Arandes, A; Thorne, C
Abstract: Background: In pregnancy early interventions are recommended for prevention of mother-to-child-transmission (PMTCT) of HIV. We examined whether pregnant women who live with HIV in Europe and are migrants encounter barriers in accessing HIV testing and care. Methods: Four cohorts within the European Pregnancy and Paediatric HIV Cohort Collaboration provided data for pooled analysis of 11 795 pregnant women who delivered in 2002–12 across ten European countries. We defined a migrant as a woman delivering in a country different from her country of birth and grouped the countries into seven world regions. We compared three suboptimal PMTCT interventions (HIV diagnosis in late pregnancy in women undiagnosed at conception, late anti-retroviral therapy (ART) start in women diagnosed but untreated at conception and detectable viral load (VL) at delivery in women on antenatal ART) in native and migrant women using multivariable logistic regression models. Results: Data included 9421 (79.9%) migrant women, mainly from sub-Saharan Africa (SSA); 4134 migrant women were diagnosed in the current pregnancy, often (48.6%) presenting with CD4 count <350 cells/µl. Being a migrant was associated with HIV diagnosis in late pregnancy [OR for SSA vs. native women, 2.12 (95% CI 1.67, 2.69)] but not with late ART start if diagnosed but not on ART at conception, or with detectable VL at delivery once on ART. Conclusions: Migrant women were more likely to be diagnosed in late pregnancy but once on ART virological response was good. Good access to antenatal care enables the implementation of PMTCT protocols and optimises both maternal and children health outcomes generally.